The identification of novel acid isostere based inhibitors of the VPS10P family sorting receptor Sortilin. Issue 11 (1st June 2017) - Andersen, Jacob Lauwring; Lindberg, Samsa; Langgård, Morten; Maltas, Philip J.; Rønn, Lars Christian Biilmann; Bundgaard, Christoffer; Strandbygaard, Dorthe; Thirup, Søren; Watson, Stephen P
Graphical abstract: Using fragment based and structure based drug discovery strategies, a series of novel Sortilin inhibitors has been identified. The inhibitors are based on the N-substituted 1, 2, 3-triazol-4-one/ol heterocyclic template. X-ray crystallography shows that the 1, 2, 3-triazol-4-one/ol acts as a carboxylic acid isostere, making a bi-dentate interaction with an arginine residue of Sortilin, an interaction which has not been previously characterised for this heterocycle. Abstract: Using fragment based and structure based drug discovery strategies a series of novel Sortilin inhibitors has been identified. The inhibitors are based on the N-substituted 1, 2, 3-triazol-4-one/ol heterocyclic template. X-ray crystallography shows that the 1, 2, 3-triazol-4-one/ol acts as a carboxylic acid isostere, making a bi-dentate interaction with an arginine residue of Sortilin, an interaction which has not been previously characterised for this heterocycle.